Intervenciones basadas en el modelo Orem para la prevención secundaria del pie diabético. - Valdiviezo Angamarca, Heidy Dayana (2024)
The main objective of this research study was to determine the nursing interventions based on Orem's systems theory and NANDA taxonomy, for secondary prevention of diabetic foot Diabetic foot is a serious complication that causes infections, ulcers and even amputation in patients with diabetes; therefore, it is crucial to take preventive measures and control the progress of the disease. This study was carried out under a retrospective, documentary scientific literature review, with a sample of 56 scientific articles reviewed considering the established inclusion and exclusion criteria. The results showed the possibility of preventing the development of diabetic foot with the application of a set of actions focused on educational support, based on these nursing systems. It is concluded that it is important to educate the patient, during the application of the three systems: totally compensatory, partially compensatory and non-compensatory, through interventions for the control of aspects related to dermatological, vascular and infection assessment, life styles and habits, attention to the spiritual and emotional environment and finally adherence to treatment, preserving their quality of life and contributing substantially to the secondary prevention of diabetic foot, to avoid serious consequences for the health of patients.